Genetic dissection of Septoria tritici blotch and Septoria nodorum blotch resistance in wheat using GWAS - Kokhmetova, Alma; Rathan, Nagenahalli Dharmegowda; Sehgal, Deepmala; Ali, Shaukat; Zeleneva, Yuliya; Kumarbayeva, Madina; Bolatbekova, Ardak; Krishnappa, Gopalareddy; Keishilov, Zhenis; Kokhmetova, Asia; Mukhametzhanov, Kanat; Bakhytuly, Kanat (Frontiers in Plant Science, 2025)
IntroductionSeptoria blotch is a globally significant disease, which ranks second in importance after wheat rusts that causes substantial yield losses. The development of Septoria blotch resistant cultivars through molecular approaches is both economical and sustainable strategy to contain the disease.MethodsFor identifying genomic regions associated with resistance to Septoria tritici blotch (STB) and Septoria nodorum blotch (SNB) in wheat, a genome-wide association study (GWAS) was conducted using a diverse panel of 191 spring and winter wheat genotypes. The panel was genotyped using DArTseq™ technology and phenotyped under natural field conditions for three cropping seasons (2019–2020, 2020–2021, and 2021–2022) and under artificially inoculated field conditions for two cropping seasons (2020–2021 and 2021–2022). Additionally, the panel was phenotyped under greenhouse conditions for STB (five mixed isolates in a single experiment) and SNB (four independent isolates and a purified toxin in five different independent experiments).Results and DiscussionGWAS identified nine marker–trait associations (MTAs), including six MTAs for different isolates under greenhouse conditions, two MTAs under natural field conditions, and one MTA under artificially inoculated field conditions. A pleiotropic MTA (100023665) was identified on chromosome 5B governing resistance against SNB isolate Pn Sn2K_USA and SNB purified toxin Pn ToxA_USA and explaining 30.73% and 46.94% of phenotypic variation, respectively. In silico analysis identified important candidate genes belonging to the leucine-rich repeat (LRR) domain superfamily, zinc finger GRF-type transcription factors, potassium transporters, nucleotide-binding site (NBS) domain superfamily, disease resistance protein, P-loop containing nucleoside triphosphate hydrolase, virus X resistance protein, and NB-ARC domains. The stable and major MTAs associated with disease resistant putative candidate genes are valuable for further validation and subsequent application in wheat septoria blotch resistance breeding.